Rancang Bangun Sistem Manajemen Gudang di PT XYZ - Muhandhis, Isnaini; Harianto Putra, Ahan Budiarta; Wibisono, Dwi Setyo; Ritonga, Alven Safik (Journal of System Engineering and Technological Innovation, 2023)
The warehouse is one of the most important parts of a company. Ineffective warehousing processes can disrupt warehouse operations. Recording warehouse transactions that are done manually will require checking one by one on the hardcopy form that has been stored. Therefore, this internship program aims to improve the performance of warehousing operations at PT XYZ. The method used in the analysis is data collection and application system design using the prototype method. The data is taken based on the results of interviews and observations in the warehouse. This activity creates a web-based warehouse management system application to help control incoming and outgoing inventory. The system built makes it easy for administrators to see the number of items made for each event. The results of black box testing show that the application has 100% functionality. The test results illustrate that the application functions properly according to user needs and has been accepted by PT XYZ